Molecular background of oligodendroglioma: 1p/19q, IDH, TERT, CIC and FUBP1. (October 2015) - Cahill, Daniel P; Louis, David N; Cairncross, John Gregory
Oligodendroglioma is the quintessential molecularly-defined brain tumor. The characteristic whole-arm loss of the long arm of chromosome 1 and the short arm of chromosome 19 (1p/19q-codeletion) within the genome of these tumors facilitated the reproducible molecular identification of this subcategory of gliomas. More recently, recurrent molecular genetic alterations have been identified to occur concurrently with 1p/19q-codeletion, and definitively identify these tumors, including mutations in IDH1/2, CIC, FUBP1, and the TERT promoter, as well as the absence of ATRX and TP53 alterations. These findings provide a foundation for the consistent diagnosis of this tumor type, upon which a generation of clinical investigators have assembled a strong evidence base for the effective treatment of this disease with radiation and chemotherapy.